A field evaluation of sodium silicate and Bacillus subtilis on the growth and yield of bananas following Fusarium wilt disease infection - Zakaria, Md Aiman Takrim; Sakimin, Siti Zaharah; Ismail, Mohd Razi; Ahmad, Khairulmazmi; Kasim, Susilawati (Multidisciplinary Digital Publishing Institute, 2023)
A field investigation was conducted in a Fusarium-infected area to evaluate the effectiveness of silicate compounds with antagonist bacteria on morpho-physiological growth performance in bananas. The roots of banana plants were treated by drenching the soil with four different treatments: control (without any treatment), CBZ (Carbendazim fungicide alone), SS + BS (integration sodium silicate with Bacillus subtilis), and CBZ + SS + BS (integration CBZ, SS, and BS). All treatments were arranged in a randomized complete block design with four replications. The results confirm that plant height, pseudo-stem diameter, and canopy diameter markedly increased from weeks 2 to 10 after transplantation. Amendment with these elements induced a higher total chlorophyll content, which contributed to the increased rate of leaf gas exchange and biochemical changes for controlling Fusarium wilt disease infection. From these findings, the CBZ + SS + BS application in the farm had significantly reduced disease incidence by 16.07 and disease severity by 14.28. The same treatment achieved the greatest disease reduction by 63.05. Therefore, the integration between CBZ + SS + BS had good significant effects in controlling Fusarium wilt disease and enhanced the morpho-physiological growth performance with an average yield production of about 24.72 kg per fruit bunch.